An ecocritical reading of Okot p’Bitek’s “Chameleon and Elephant” - Rose Opondo; Tobias Odongo (Tydskrif vir letterkunde, 2025)
In this article, we undertake an eco-critical analysis of an Acholi traditional oral folktale rewritten by Okot p’Bitek in his oral literature text Hare and Hornbill as an allegorical narrative with the title “Chameleon and Elephant”. We do this to examine the Acoli community’s perceptions of the natural environment and its sustenance of life. Through close reading and content analysis within the paradigm of ecological considerations, in this article we show how interconnected and symbiotic human, animal, and plant worlds are, and how destroying a segment leads to the destruction of all three. The story we analyse presents the sober topic of nature’s wrath at its abuse through the structural and psychological dictates of the creative oral narrative. We place oral literature at the centre of exploring the needed mind shifts in environmental conservation. We conclude by arguing that the narrative’s central argument is that conservation demands intelligence and humility rather than force and arrogance, parallel to traditional African approaches to co-existence with the environment and in direct opposition to modern supremacist exploitation and degradation of the same environment.